2020
DOI: 10.1155/2020/1373087
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Future Terrorist Activities Using Deep Neural Networks

Abstract: One of the most important threats to today’s civilization is terrorism. Terrorism not only disturbs the law and order situations in a society but also affects the quality of lives of humans and makes them suppressed physically and emotionally and deprives them of enjoying life. The more the civilizations have advanced, the more the people are working towards exploring different mechanisms to protect the mankind from terrorism. Different techniques have been used as counterterrorism to protect the lives of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 40 publications
0
25
0
2
Order By: Relevance
“…Derin sinir ağlarını kullanarak terör faaliyetlerinin tahminini yapmaya çalışan bir çalışmada, terör faaliyetinin davranışını anlamak için saldırının türünün intihar olup olmadığı, saldırının başarılı olup olmadığı, ne tür bir silah kullanılabileceği, hangi bölgenin hedef alınabileceği ve ne tür bir teröristin kullanılacağına dayalı beş farklı faktör belirlenmektedir [16]. Çalışmada tek katmalı sinir ağı ve derin sinir ağı tabanlı modeller geliştirilerek, derin sinir ağına dayalı modelin başarı oranının daha yüksek olduğu görülmüştür [16].…”
Section: İlgili çAlışmalarunclassified
See 1 more Smart Citation
“…Derin sinir ağlarını kullanarak terör faaliyetlerinin tahminini yapmaya çalışan bir çalışmada, terör faaliyetinin davranışını anlamak için saldırının türünün intihar olup olmadığı, saldırının başarılı olup olmadığı, ne tür bir silah kullanılabileceği, hangi bölgenin hedef alınabileceği ve ne tür bir teröristin kullanılacağına dayalı beş farklı faktör belirlenmektedir [16]. Çalışmada tek katmalı sinir ağı ve derin sinir ağı tabanlı modeller geliştirilerek, derin sinir ağına dayalı modelin başarı oranının daha yüksek olduğu görülmüştür [16].…”
Section: İlgili çAlışmalarunclassified
“…Derin öğrenme, bu tahminleri verimli bir şekilde yapabilmekte ve bireylerin hayatlarını korumak için yeni yöntemlerin geliştirilmesine yardımcı olmaktadır. Bu yöntemler yardımıyla, bir terör eylemi fiilen gerçekleşmeden önce güvenlik güçlerinin terör olayları ile başa çıkmasını sağlanabilmektedir [16].…”
Section: Introductionunclassified
“…In another research [23], GPU-based Hadoop framework is used for evaluation of Canny Edge Detection algorithm using the default scheduler of Hadoop for workload distribution and has demonstrated two times performance improvement than HIPI-based image processing [24]. In [25,26], face detection in video frames is performed by using CUDA-based Hadoop framework. It is observed that actual data processing takes 55% of the processor time, and the remaining 45% is wasted as idle or busy in performing other management activities.…”
Section: Related Workmentioning
confidence: 99%
“…Apriori algorithm was firstly used to extract the behavioral patterns, and then, Naïve Bayes classifier was used for decision making for trustworthiness of users. Uddin et al [14] proposed an approach for the detection of terrorist activities.…”
Section: Related Workmentioning
confidence: 99%